The last tribes on Earth journeys among the world's most threatened cultures - Raffaele, Paul (Sydney Pan Macmillan Australia, 2003)
The author's account of his journeys to some of the world's most isolated and endangered peoples and cultures.

An account of Raffaele's journeys in Papua, the Central African Republic, the Himalayan Kingdom of Mustang and the Australian Outback.
Keywords: Raffaele, Paul -- Travel; Voyages and travels; Journalists -- Travel